SENYAWA PENGKUPLING α-NAFTHILAMIN UNTUK VALIDASI METODE SPEKTROFOTOMETRI PENENTUAN NITRIT (〖〖NO〗_2〗^-) DI DALAM AIR - Maruni Wiwin Diarti; I Gusti Ayu Nyoman Danuyanti; I Gede Billy Sumantri (poltekkes kemenkes mataram, 2015)
Abstract: Validation of analytical methods need to be conducted to determine the feasibility of the method when the method is newly developed or modified. Determination of nitrite in water-based Cupling diazotized reaction has been developed in various fields. Many modifications have been carried out primarily in the selection of the source of the diazonium salt compound or compounds that can cupling. The this study was to determine the validity of the determination of nitrite in water by spectrophotometric method cupling compound α-nafthilamin. This study is a pre-experiments with experimental units and large units based guidelines experimental validation of analytical methods. The results show the value of 0.995 linearity, limit of detection (LOD) 0.039 ppm, 0.882 sensitivity, precision 1.38%, and 100.37% accuracy rate. The conclusion of this study is the method of spectrophotometric determination of nitrite in water using compound α-nafthilamin cupling valid for determining the concentration of nitrite in the water with a minimum detection limit of 0.039 ppm.